Addition type high-bonding-strength heat-conducting adhesive and preparation method thereof
Through the synthesis of solvent-free addition-molded thermal adhesives, the problems of insufficient bonding strength and low molecular volatility of existing thermal adhesives are solved by using raw materials such as (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane and surface-modified thermal fillers, and the problems of insufficient bonding strength and low molecular volatility are achieved, and both high bonding strength and thermal conductivity are achieved.
Patent Information
- Application Number
- CN202411865615.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-28
AI Technical Summary
The existing thermally conductive adhesives produce low molecular substances during the curing process, have a large shrinkage rate, and insufficient adhesive strength to electronic components and substrates, resulting in limited application.
Solvent-free addition-molded thermally conductive adhesive is used to form a single-component adhesive with high bond strength and thermal conductivity by synthesizing (2,3-epoxypropoxy)propyl-terminated polymethylvinyl siloxane and surface-modified thermal fillers.
It achieves high bonding strength, high thermal conductivity and superior insulation after curing, avoids the problems of low molecular volatility and large shrinkage, and is suitable for thermal bonding of electronic devices.
Smart Images

Figure BDA0005194257710000011 
Figure BDA0005194257710000051 
Figure BDA0005194257710000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives and relates to a thermally conductive adhesive, in particular to an addition-type thermally conductive adhesive with high bonding strength and a preparation method thereof. Background Art
[0002] When selecting thermally conductive adhesives for electronic devices, the following aspects should be considered: (1) The product needs to have good thermal conductivity and heat dissipation; (2) The product needs to have good insulation; (3) The product needs to have good strength; (4) No small molecules are generated during the curing process; (5) After curing, the product needs to have good bonding strength with electronic components and base materials.
[0003] An ideal thermally conductive adhesive is a silicone with good thermal conductivity and bonding properties. It is mainly used for heat conduction and heat transfer in electronic components such as IC chips, transistors, processors, etc. to improve heat dissipation efficiency. At present, the most common thermally conductive silicones on the market include thermal grease, thermal gel, thermal pads, thermal adhesives, etc. Among them, thermal grease, thermal gel, and thermal pads have no adhesion to electronic components and substrates, and only have heat dissipation functions; while thermally conductive adhesives with heat transfer and bonding properties include addition type and condensation type systems: the addition type thermally conductive adhesive does not produce low molecular substances during the curing process, and the shrinkage rate is extremely low, but ordinary addition type thermally conductive adhesives do not have a good bonding effect on components and substrates, and the strength of the colloid will be relatively poor when the proportion of thermal conductive fillers is relatively large, which has limitations in application; condensation type thermally conductive adhesives generally have good adhesion to the substrate, but the curing process releases low molecules and has disadvantages such as large shrinkage rate. Therefore, the thermally conductive silicones on the market are not ideal thermally conductive adhesives. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a solvent-free addition-type high bonding strength thermally conductive adhesive, which has excellent cured bonding strength, good colloid strength, high thermal conductivity and excellent insulation. The addition-type thermally conductive adhesive is mainly used for bonding and heat dissipation of electronic devices (because the thermally conductive adhesive has strong bonding strength with electronic components and substrates), and can play the role of sealing, moisture-proof, collision-proof, and protecting electronic components.
[0005] In order to achieve the above object, the present invention provides an addition-type high bonding strength thermally conductive adhesive, which comprises the following raw material components in parts by weight:
[0006] 75-90 parts of (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane;
[0007]
[0008] Optimally, the (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane is prepared by the following method:
[0009] S11. Add dimethyldiethoxysilane, methylvinyldimethoxysilane, purified water, an organic solvent and an acidic catalyst to a reflux reaction device and mix them evenly; the organic solvent is a mixture of one or more selected from xylene, cyclohexane and n-ethane, and the acidic catalyst is a mixture of one or more selected from hydrochloric acid, oxalic acid, sulfuric acid and trifluoromethanesulfonic acid;
[0010] S12. The mixture of step S11 is hydrolyzed and refluxed at 75°C to 90°C for 3 to 5 hours;
[0011] S13. Open the water separator in the reflux reaction device, discharge the alcohol byproducts of the reaction and retain the organic solvent, and divide the water for 8 to 12 hours;
[0012] S14. Standing and stratifying, separating the acid water in the lower layer; heating to 100-130°C to remove the solvent, continuing the reaction for 4-6 hours at a vacuum degree of ≤-0.095MPa, venting to normal pressure, adding γ-(2,3-epoxypropoxy)propyltrimethoxysilane dropwise, and reacting for 3-6 hours;
[0013] S15. Add sodium bicarbonate and stir for 1 to 2 hours, raise the temperature to 145 to 155°C, and evacuate until no droplets are discharged when the vacuum degree is ≤-0.095 MPa.
[0014] Furthermore, the chemical structural formula of the (2,3-epoxypropoxy)propyl terminated polymethylvinylsiloxane is: CH2OCHCH2OCH2CH2CH2Si(CH3O)2[SiO(CH3)2] m [SiOCH3Vi] n Si(CH3O)2CH2CH2CH2OCH2CHOCH2, wherein 10≤m≤100, 1≤n≤20 and m and n are integers.
[0015] Optimally, the hydrogen-containing silicone oil is a mixture of one or more selected from pendant hydrogen silicone oil and terminal hydrogen silicone oil.
[0016] Optimally, the surface-modified thermally conductive filler is a spherical composite alumina surface-modified with vinyl siloxane.
[0017] Furthermore, the vinylsiloxane surface-modified spherical composite alumina is prepared by the following method:
[0018] S21. Adding compounded spherical alumina to the reaction device; the compounded spherical alumina is a compound selected from a plurality of BAK-2, BAK-5 and BAK-10-35C;
[0019] S22. Start the heating device to heat, turn on the stirrer, and when the temperature reaches 100 to 120 ° C, the vinyl siloxane is sprayed into the reaction device through a spray device for less than 1 hour; the vinyl siloxane is vinyl trimethoxysilane or vinyl triethoxysilane;
[0020] S23. After spraying the vinyl siloxane, the reaction was allowed to proceed for 1 to 5 hours; the temperature was then raised to 130 to 150 ° C, and the reaction was continued for 1 to 3 hours;
[0021] S24. After the reaction is completed, stop heating and wait for cooling.
[0022] Optimally, the toner is a mixture of one or more selected from inorganic toner and organic toner.
[0023] Optimally, the platinum catalyst is a platinum complex having a platinum content of 3000 to 10000 ppm.
[0024] Optimally, the inhibitor is an organic compound containing N, P and S, or a heavy metal ion compound containing Sn, Pb, Hg, Bi and As, or a compound containing alkynyl and polyvinyl groups.
[0025] Another object of the present invention is to provide a method for preparing the above-mentioned addition-type high-bonding strength thermally conductive adhesive, comprising the following steps:
[0026] The (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane is mixed with the color powder, and then stirred and mixed with hydrogen-containing silicone oil, surface-modified thermal conductive filler, and polymerization inhibitor, and then a platinum catalyst is added and stirred and mixed to form a single-component adhesive.
[0027] The addition-type high-bonding-strength thermally conductive adhesive of the present invention combines hydrogen-containing silicone oil, color powder, platinum catalyst, polymerization inhibitor, etc. with specific (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane and surface-modified thermally conductive filler, does not require the use of solvents, has the advantages of excellent cured bonding strength, good colloid strength, high thermal conductivity, and excellent insulation; and can make the adhesive have bonding groups, thereby improving the bonding performance of the product; the residual methoxy group of γ-(2,3-epoxypropoxy)propyltrimethoxysilane generates hydroxyl value after later hydrolysis, which will further improve the bonding strength between the product and the electronic components and the substrate; in addition, after the surface of alumina is modified by vinyl siloxane, the vinyl on the surface of the filler undergoes a cross-linking reaction with the silicon-hydrogen bond of the product, which can further improve the strength of the thermally conductive adhesive and avoid the problem of poor colloid strength due to excessive proportion of filler. DETAILED DESCRIPTION
[0028] The invention discloses an addition-type high-bonding-strength heat-conductive adhesive, which comprises the following raw material components in parts by weight: 75-90 parts of (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane; 10-25 parts of hydrogen-containing silicone oil; 1000-1300 parts of surface-modified heat-conductive filler; 0.01-1 part of color powder; 0.01-1 part of platinum catalyst; and 0.01-0.5 part of polymerization inhibitor. The combination of hydrogen-containing silicone oil, color powder, platinum catalyst, polymerization inhibitor, etc. with specific (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane and surface-modified thermal conductive filler does not require the use of solvents and has the advantages of excellent cured bonding strength, good colloid strength, high thermal conductivity and excellent insulation. It can also make the adhesive have bonding groups, thereby improving the bonding performance of the product. The residual methoxy group of γ-(2,3-epoxypropoxy)propyltrimethoxysilane will generate hydroxyl value after hydrolysis in the later stage, which will further improve the bonding strength between the product and electronic components and substrates. In addition, after the surface of alumina is modified by vinyl siloxane, the vinyl on the surface of the filler undergoes a cross-linking reaction with the silicon-hydrogen bond of the product, which can further improve the strength of the thermal conductive adhesive.
[0029] The (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane is prepared according to the following method: S11. dimethyldiethoxysilane, methylvinyldimethoxysilane, purified water, an organic solvent and an acid catalyst are added to a reflux reaction device and mixed evenly; the organic solvent is a mixture of one or more selected from xylene, cyclohexane and n-ethane, and the acid catalyst is a mixture of one or more selected from hydrochloric acid, oxalic acid, sulfuric acid and trifluoromethanesulfonic acid; S12. the mixture of step S11 is hydrolyzed and refluxed at 75°C to 90°C for 3 to 5 hours; S13. the reflux reaction is opened. The water separator in the device should be used to discharge the alcohol byproducts and retain the organic solvent, and the water separation should be 8 to 12 hours; S14. Let it stand for stratification and separate the acid water in the lower layer; raise the temperature to 100 to 130°C to remove the solvent, continue to react for 4 to 6 hours at a vacuum degree of ≤-0.095MPa, vent to normal pressure, drop γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), and react for 3 to 6 hours; S15. Add sodium bicarbonate and stir for 1 to 2 hours, raise the temperature to 145 to 155°C, and evacuate to remove the liquid at a vacuum degree of ≤-0.095MPa until no droplets are discharged. The above-mentioned (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane is a mixture, but its general chemical structure formula can be roughly represented as:
[0030] CH2OCHCH2OCH2CH2CH2Si(CH3O)2[SiO(CH3)2] m [SiOCH3Vi] nSi(CH3O)2CH2CH2CH2OCH2CHOCH2, wherein 10≤m≤100, 1≤n≤20 and m and n are integers. The hydrogen-containing silicone oil is a mixture of one or more selected from side hydrogen silicone oil and terminal hydrogen silicone oil. The surface-modified thermal conductive filler is a spherical composite alumina surface-modified with vinyl siloxane. The spherical composite alumina modified with vinyl siloxane surface is prepared according to the following method: S21. Add the composite spherical alumina into the reaction device; the composite spherical alumina is selected from BAK-2, BAK-5 and BAK-10-35C; S22. Start the heating equipment to heat, turn on the stirrer, and when the temperature reaches 100-120°C, spray the vinyl siloxane into the reaction device through the spray device, and the time is controlled within 1 hour; the vinyl siloxane is vinyl trimethoxysilane or vinyl triethoxysilane; S23. After spraying the vinyl siloxane, react for 1-5 hours; then raise the temperature to 130-150°C, and continue to react for 1-3 hours; S24. After the reaction is completed, stop heating and wait for cooling. The toner is a mixture of one or more selected from inorganic toner and organic toner. The platinum catalyst is a platinum complex with a platinum content of 3000-10000ppm. The polymerization inhibitor is an organic compound containing N, P and S, or a heavy metal ion compound containing Sn, Pb, Hg, Bi and As, or a compound containing alkynyl and polyvinyl.
[0031] The preparation method of the above-mentioned addition-type high-bonding strength thermally conductive adhesive comprises the following steps: mixing the (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane with the color powder in a formulated amount, stirring and mixing with hydrogen-containing silicone oil, surface-modified thermally conductive filler, and polymerization inhibitor, and then adding a platinum catalyst and stirring and mixing to form a single-component adhesive.
[0032] In order to enable those skilled in the art to better understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained under the premise of equivalent changes and modifications made by ordinary technicians in the field should belong to the scope of protection of the present invention.
[0033] Example 1
[0034] This embodiment provides a (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane and a preparation method thereof, which are specifically as follows:
[0035] S11) adding 2800 g of dimethyldiethoxysilane, 200 g of methylvinyldimethoxysilane, 1800 g of purified water, 2000 g of cyclohexane and 10 g of trifluoromethanesulfonic acid into a 10000 ml four-necked flask and mixing well;
[0036] S12) heating to 77°C and performing hydrolysis reflux reaction for 4 hours;
[0037] S13) opening the water separator in the reaction device, discharging the reaction alcohol by-products, and refluxing the water separator for 10 hours;
[0038] S14) standing to separate the layers, separating the pure water in the lower layer, slowly heating to 100-130°C to remove the solvent, evacuating to a vacuum (-0.099 MPa, measured by conventional instruments, the same below) and continuing the reaction for 6 hours; slowly venting to normal pressure, dropping 50 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), and reacting for 3 hours;
[0039] S15) add 5 g of sodium bicarbonate and stir for 1 hour, raise the temperature to 150±5°C and degas in vacuum (-0.099 MPa) until no droplets are discharged, and about 1200 g of (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane having an olefin content of 0.18% (wt%) and a viscosity of 1100 CPs can be obtained (the chemical structure formula of the (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane can be expressed as:
[0040] CH2OCHCH2OCH2CH2CH2Si(CH3O)2[SiO(CH3)2] m [SiOCH3Vi] n Si(CH3O)2CH2CH2CH2OCH2CHOCH2, wherein 10≤m≤100, 1≤n≤20 and m and n are integers; it is usually a mixture).
[0041] Example 2
[0042] This embodiment provides a spherical composite alumina surface modified with vinyl siloxane and a preparation method thereof, which are specifically as follows:
[0043] S21) Add 200 g of BAK-2 (Shanghai Baitu, the same below), 500 g of BAK-5, and 1300 g of BAK-10-35C (all of which are spherical alumina) into the reaction device in a mass ratio of 10:25:65, and start a stirrer to stir evenly;
[0044] S22) starting the heating device to heat, when the temperature reaches 100-120° C., spraying 20 g of vinyltrimethoxysilane evenly into the reaction device through a spray device, and the time is controlled to be completed within 30 minutes;
[0045] S23) After spraying vinyltrimethoxysilane, stirring at a constant temperature for 3 hours, then slowly raising the temperature to 130-150° C., and continuing stirring at a constant temperature for 2 hours;
[0046] S24) After the reaction is completed, the heating is stopped, and the spherical alumina surface-modified with vinyltrimethoxysilane is obtained after cooling.
[0047] Embodiment 3-7
[0048] Examples 3-7 respectively provide an addition-type high-bonding strength thermally conductive adhesive, and the specific dosage is shown in Table 1; their specific preparation methods are consistent, as follows: (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane (in Example 1) is mixed with carbon black powder by three rollers, and stirred evenly with side hydrogen silicone oil, terminal hydrogen silicone oil, vinyltrimethoxysilane surface-modified alumina (in Example 2), and inhibitor (acetylene cyclohexanol), and then 3000ppm of platinum catalyst (Sineng, CAS No. 68478-92-2) is added and stirred evenly to form a single-component adhesive. The proportions of each material are shown in Table 1.
[0049] Table 1 Composition of the addition type high bonding strength thermal conductive adhesive in Examples 3-7
[0050]
[0051]
[0052] Comparative Examples 1-6
[0053] Commercially available 1000CP vinyl-terminated dimethylpolysiloxane (McCarthy, CAS No. 68083-19-2), GD-S403Z (alumina, Guangdong Jinge New Materials), unsurface-modified spherical alumina (Bai Tu), tackifier, etc. were mixed according to the method disclosed in the above embodiment to prepare an adhesive. The proportions of each material are shown in Table 2.
[0054] Table 2 Composition of adhesives in Comparative Examples 1-6
[0055]
[0056]
[0057] The adhesives in Examples 3-7 and Comparative Examples 1-6 were subjected to performance tests, and the results are shown in Table 3.
[0058] Table 3 Performance of adhesives in various examples
[0059]
[0060]
[0061]
[0062] Note:
[0063] 1. Test after baking at 150℃ for 1 hour.
[0064] 2. The test standard for viscosity is GB / T 10247-2008; the test standard for surface drying time is GB / T 13477.5-2002B method; the test standard for hardness is GB / T 531-1999; the test standard for peel strength is GB / T2792-2014; the test standard for thermal conductivity is: ASTM D5470-17; the test standard for tensile strength is GB / T 528-2009; the test standard for elongation is GB / T 528-2009; the test method for BLT is: apply glue on two glass slides, press a 1Kg weight, and then measure the thickness added by the two glass slides; the test standard for dielectric strength is: GB / T 1408.1-2006; the test standard for volume resistivity is: GB / T 1410-2006; the test standards for loss factor (50Hz) and dielectric constant (50Hz) are: GB / T1409-2006.
[0065] It can be concluded from Table 3 that, in Examples 3 to 5, as the proportion of (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane increases, the hardness of the product is improved, the colloid strength is increased, but the viscosity becomes thicker. Considering the comprehensive performance in all aspects, the amount of (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane in Example 4 is slightly better; in Examples 4, 6, and 7, increasing the proportion of thermally conductive fillers can improve the thermal conductivity of the product, but the more fillers are added, the more obvious the increase in the viscosity of the product will be, and too much filler will reduce the bonding strength of the product. From the comprehensive performance of Examples 2 to 7, the formula of Example 6 is the best. The difference between Comparative Examples 1 and 2 and Example 6 is that in the formulas of Comparative Examples 1 and 2, unsurface-modified spherical alumina is used, and the amount of unmodified alumina added is low and cannot be fully added; in Comparative Example 3, ordinary surface-modified spherical alumina is used. Since there is no group on the surface of the filler that can participate in cross-linking with the components, the filler accounts for a large proportion, and the strength of the adhesive after curing is poor, and there is no bonding strength; in Comparative Examples 4 to 6, ordinary vinyl silicone oil is used instead of (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane. After the colloid is cured, there is no bonding performance. After directly adding the tackifier coupling agent, since it fails to cross-link through the adhesive reaction and the small molecule coupling agent is difficult to react, no bonding effect can be produced after adding the tackifier coupling agent, and doubling the platinum catalyst also fails to produce a bonding effect.
[0066] The invention discloses an addition-type high bonding strength thermally conductive adhesive prepared by synthesizing (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane and vinylsiloxane surface-modified alumina. The adhesive has the advantages of good insulation, high colloid strength, high thermal conductivity, low temperature difference thermal resistance, high cured bonding strength, no small molecule volatilization during curing, etc. The adhesive is an ideal thermally conductive adhesive and can be widely used in thermal conductive bonding of electronic devices.
[0067] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. At the same time, the above description should be understandable and implementable for those with ordinary knowledge in the relevant technical field. Therefore, other equivalent changes or modifications that do not deviate from the concept disclosed by the present invention should be included in the scope of protection of the present invention.
Claims
1. An addition type high bonding strength thermal conductive adhesive, characterized in that: It includes the following raw material components in parts by weight: 75-90 parts of (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane; 10-25 parts of hydrogen silicone oil; 1000~1300 parts of surface modified thermal conductive filler; Color powder 0.01~1 part; Platinum catalyst 0.01~1 part; Inhibitor 0.01~0.5 parts.
2. The addition-type high bonding strength thermally conductive adhesive according to claim 1, characterized in that: The (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane is prepared by the following method: S11. Add dimethyldiethoxysilane, methylvinyldimethoxysilane, purified water, an organic solvent and an acidic catalyst to a reflux reaction device and mix them evenly; the organic solvent is a mixture of one or more selected from xylene, cyclohexane and n-ethane, and the acidic catalyst is a mixture of one or more selected from hydrochloric acid, oxalic acid, sulfuric acid and trifluoromethanesulfonic acid; S12. The mixture of step S11 is hydrolyzed and refluxed at 75°C to 90°C for 3 to 5 hours; S13. Open the water separator in the reflux reaction device, discharge the alcohol byproducts of the reaction and retain the organic solvent, and divide the water for 8 to 12 hours; S14. Allow to stand and separate, remove the acid water in the lower layer; raise the temperature to 100-130°C to remove the solvent, continue the reaction for 4-6 hours at a vacuum degree of ≤-0.095MPa, vent to normal pressure, add γ-(2,3-epoxypropoxy)propyltrimethoxysilane dropwise, and react for 3-6 hours; S15. Add sodium bicarbonate and stir for 1-2 hours, raise the temperature to 145-155°C, and evacuate the mixture until no droplets are discharged when the vacuum degree is ≤-0.095 MPa.
3. The addition-type high bonding strength thermally conductive adhesive according to claim 1 or 2, characterized in that: The chemical structural formula of the (2,3-epoxypropoxy)propyl terminated polymethylvinylsiloxane is: CH2OCHCH2OCH2CH2CH2Si (CH3O)2[SiO(CH3)2] m [SiOCH3Vi] n Si(CH3O)2CH2CH2CH2OCH2CHOCH2, wherein 10≤m≤100, 1≤n≤20 and m and n are integers.
4. The addition-type high bonding strength thermally conductive adhesive according to claim 1, characterized in that: The hydrogen-containing silicone oil is a mixture of one or more selected from pendant hydrogen silicone oil and terminal hydrogen silicone oil.
5. The addition-type high bonding strength thermally conductive adhesive according to claim 1, characterized in that: The surface-modified thermal conductive filler is a spherical composite alumina surface-modified with vinyl siloxane.
6. The addition-type high bonding strength thermally conductive adhesive according to claim 5, characterized in that: The spherical composite alumina surface modified with vinyl siloxane is prepared by the following method: S21 adding a good compound spherical alumina in the reaction apparatus; the compounded spherical alumina is selected from a variety of compounded BAK-2, BAK-5 and BAK-10-35C; S22. Start the heating device to heat, turn on the stirrer, when the temperature reaches 100 ~ 120 ℃, through the spray device, the vinyl siloxane is sprayed into the reaction device, the time is controlled within 1 hour; the vinyl siloxane is vinyl trimethoxysilane fans or vinyl triethoxysilane; S23. After spraying the vinyl siloxane, react for 1 to 5 hours; then raise the temperature to 130 to 150°C and continue to react for 1 to 3 hours; S24. After the reaction is completed, stop heating and wait for cooling.
7. The addition-type high bonding strength thermally conductive adhesive according to claim 1, characterized in that: The toner is a mixture of one or more selected from inorganic toner and organic toner.
8. The addition-type high bonding strength thermally conductive adhesive according to claim 1, characterized in that: The platinum catalyst is a platinum complex with a platinum content of 3000-10000 ppm.
9. The addition-type high bonding strength thermally conductive adhesive according to claim 1, characterized in that: The polymerization inhibitor is an organic compound containing N, P and S, or a heavy metal ion compound containing Sn, Pb, Hg, Bi and As, or a compound containing alkynyl and polyvinyl.
10. The method for preparing the addition type high bonding strength thermal conductive adhesive according to any one of claims 1 to 9, comprising the following steps: The (2,3-epoxypropoxy)propyl-terminated polymethylvinylsiloxane is mixed with the color powder, and then stirred and mixed with hydrogen-containing silicone oil, surface-modified thermal conductive filler, and polymerization inhibitor, and then a platinum catalyst is added and stirred and mixed to form a single-component adhesive.